An Examination of the Bond Characteristics between Concrete and Deformed Reinforcing Bars - Nugroho, Danang Hadi; Wijanarko, Danang; Zahir, Lutfan Anas (Jurnal Teknik Sipil Info Manpro, 2025)
The most critical performance of a reinforced concrete composite structure is the binding behavior between its components. Optimal bond behavior is essential for guaranteeing the service performance of reinforced concrete structures, influencing the structure's performance throughout its life cycle. In practical structural analysis, it is commonly accepted that the two do not generate relative slippage, leading to discrepancies between the studied structure and the real engineering conditions. Currently, numerous scholars worldwide have employed diverse testing methodologies, thoroughly examining various aspects influencing the binding behavior between bent rebar and concrete, resulting in numerous results. This paper provides a comprehensive review of the research status regarding the bonding performance of reinforced concrete, grounded in the pertinent findings of various scholars. It examines the bond mechanism, the experimental methodologies for assessing bond behavior, and the factors influencing this behavior. It is anticipated that it will serve as a reference for scholars examining the bond behavior of reinforced concrete in the future.